GEREJA SEBAGAI KELUARGA RUMAH TANGGA DAN RELEVANSINYA TERHADAP PENDIDIKAN AGAMA KATOLIK: KAJIAN PASTORAL DI PAROKI AIMUTIN - Duka, Gerardus Bernadus; Bele, Graciana Amanda; Sasi, Viktor Doddy Sau; Masan, Valentinus Kopong (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The family is not only seen as the smallest unit of society, but also as the domestic Church (ecclesia domestica), where faith is instilled, lived, and passed on. In light of Catholic Church teachings, the family is the primary basis of Catholic Religious Education, shaping the character and spirituality of the congregation from an early age. However, amidst social dynamics and the rapid development of digital technology, the congregation's awareness of the family's identity as a domestic Church is weakening. This study aims to analyze the dynamics of congregational formation and pastoral practices in realizing the Church as a domestic family and their relevance to Catholic Religious Education in Aimutin Parish, Dili. The study used a qualitative-descriptive method with data collection techniques through interviews, observation, and documentation. The focus of the study includes identifying pastoral challenges, development strategies, implementation of family programs, and the roles of families and pastors in church life. The results show that ethnic diversity, low congregational participation, minimal systematic faith formation, socio-economic challenges, and the influence of digital culture are the main obstacles to strengthening the family as a domestic Church. This situation has a direct impact on the effectiveness of Catholic Religious Education in the family environment. Therefore, this study emphasizes the importance of ongoing faith formation, the development of a digital-based pastoral approach, and the empowerment of families as the primary subjects of faith education and implementers of the Church's mission in daily life. Keywords: Domestic Church; Ecclesia Domestica; Catholic Religious Education; Faith Formation; Family Pastoral Care; Aimutin Parish